Solutions notes on clean textile waste - Jordão, C. (2019)
In the contemporary moment, the textile and clothing industries are practicing and passing through a transition period into their management systems (specially on waste) due to consumer change in social behavior, which can, potentially, ensure the sustenance and well-being for the generations to come. Into this context, the present research aims to analyze sustainable strategies that are being implemented by the textile and clothing industry, searching for solutions for the management of clean solid waste, concerns with processed and non-processed textile fibers waste. In addition, it is mapped and pointed some gaps for the development of further and future researches. In order to achieve the proposed goal, it was searched a rigorous selection of projects and studies that expressed innovative solutions, concerning practices and theories application about the possibilities in the management of the clean textile waste. The results are optimistic, as they already point to some real action in terms of companies aware of the need for sustainable practices in their production.